BNC210: an investigational α7-nicotinic acetylcholine receptor modulator for the treatment of anxiety disorders. (3rd April 2023) - Hampsey, Elliot; Perkins, Adam; Young, Allan H.
ABSTRACT: Introduction: Anxiety disorders are common, disabling psychiatric conditions associated with excessive worry, irritability, and physiological symptoms of stress. Following insufficient response to psychological therapies, first-line pharmacological treatments for anxiety disorders suffer from inconsistent efficacy, addiction, and intolerable side-effect profiles (e.g. sedation), especially when used inappropriately or contrary to evidence-based guidelines. Developing anxiolytics acting via cholinergic modulation may provide novel options for the treatment of anxiety disorders, without the drawbacks of existing anxiolytics. Areas covered: We review pharmacological treatment of anxiety disorders and proposed mechanisms of action in relation to the associated neural circuitry. We then consider the mechanism of action, pharmacodynamics, and pharmacokinetics of the negative-allosteric modulator of the alpha7 nicotinic receptor BNC210, an investigational anxiolytic so far employed in studies of those with social anxiety disorder, post-traumatic stress disorder, and agitation in hospitalized elderly. Lastly, we consider the environment of competitor compounds for this indication, and BNC210ʹs place within it, in both the present and near-future. Expert opinion: : There is a relative paucity of data regarding BNC210, albeit the small amount of mostly non-peer reviewed data indicate it is a well-tolerated, effective anxiolytic. Phase III trials are required for proper appraisal of its utility.